Snoring time versus snoring intensity: Which parameter correlates better with severity of obstructive sleep apnea syndrome? - Souha Kallel; Khouloud Kchaou; Asma Jameleddine; Moncef Sellami; Malek Mnejja; Ilhem Charfeddine (Lung India, 2020)
Objective: The relationship between the severity of obstructive sleep apnea syndrome (OSAS) and both snoring intensity and rate measured objectively has not been sufficiently investigated. The aim of this study was to evaluate the relationship between severity of OSAS and snoring parameters including snoring intensity and rate. Patients and Methods: A total of 150 records of individuals who complained of snoring were analyzed. Patients were classified into four groups according to apnea–hypopnea index (AHI). Polygraphy recordings including the snoring intensity and the snoring rate (defined as the percentage of snoring time during the total sleep time) and the clinical data were compared and analyzed. Results: AHI was significantly correlated, respectively, with snoring rate (r = 0.341; P < 0.0001) and maximal intensity of snoring (r = 0.362; P < 0.0001). However, no correlation was found between the average intensity of snoring and AHI (P = 0.33). When assessing each respiratory event individually, snoring rate was more correlated with hypopnea index (r = 0.424; P < 0.0001) than with AI (r = 0.233; P = 0.004). The snoring rate (%) in the severe OSAS group (31.79 ± 19.3) was significantly higher than that in the mild OSAS group (18.02 ± 17; P = 0.001) and the control group (17 ± 16.57; P = 0.011). Similarly, the maximal intensity of snoring (db) in the severe OSAS group (90.45 ± 13.79) was higher than that in the mild OSAS group (86.46 ± 15.07; P = 0.006) and the control group (84.75 ± 6.65; P < 0.001). Conclusion: The snoring rate and maximal intensity of snoring correlate better with the severity of OSAS than average snoring intensity.